RJ style of speaking: is it creating a sub-culture of Bangaldeshi youth? - Tinny, Farhana Zamil (BRAC University, 2011)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2010.